Adoption and application of ICTs in academic libraries in Oyo state, Nigeria (2013)
The study investigated the extent to which government - owned tertiary institutions’ libraries in Oyo State have deployed ICTs in their operations. The descriptive survey research design was adopted for the study. Purposive sampling technique was used to select six (6) libraries from the eight (8) tertiary institutions’ libraries in Oyo state, Nigeria. Total enumeration was used to cover all the one hundred and fifty five (155) Professional and para-professional library personnel working in the selected libraries. Questionnaire was the main instrument for data collection. However, information gathered from interviews and observations were used to complement what the questionnaire provided. Data gathered were analysed by using descriptive statistics of simple percentages and frequency counts. The findings revealed that in all the libraries, Computers, Internet, photocopiers, and printers were ICT facilities readily available for use. Also, Internet Services were found to be the most common ICT - based library and information Services rendered. Based on the findings of the study, it was recommended that the government and the parent institutions should support the ICT drive of the libraries by providing all the necessary human, technical and financial support for full application of ICTs in the libraries.